2007
DOI: 10.1111/j.1365-2648.2007.04382.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Caring for’ behaviours that indicate to patients that nurses ‘care about’ them

Abstract: The findings suggest that patients believe that caring is demonstrated when nurses respond to specific requests. Patient satisfaction with the service is more likely to be improved if nurses can readily adapt their work to accommodate patients' requests or, alternatively, communicate why these requests cannot be immediately addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 18 publications
0
45
0
6
Order By: Relevance
“…In this investigation, the nurses' performance and patients' fulfillment have not been significantly correlated. This might be explained by the discoveries of Henderson et al (2007), who found a feeble connection because of bureaucratic requests, expanded workload, and diminished staffing levels. Vast quantities of patients and nurses invest a large portion of their time and vitality to play out doctor's requests, composing the reports and doing some secretarial occupations.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, the nurses' performance and patients' fulfillment have not been significantly correlated. This might be explained by the discoveries of Henderson et al (2007), who found a feeble connection because of bureaucratic requests, expanded workload, and diminished staffing levels. Vast quantities of patients and nurses invest a large portion of their time and vitality to play out doctor's requests, composing the reports and doing some secretarial occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Attree (2001) found, in a qualitative study of patients' and relatives' perspective on good and not so good care, that the nature of the care provided and the interpersonal qualities of caring were the major themes. Henderson et al (2007) found, through both observation and direct questions, that patients felt cared for when nurses responded to specific requests. Studies of nurses have shown that nurses consistently emphasize the humanistic side of the caring relationship rather than the technical aspects (Bassett, 2002;Bertero, C., 1999;Dyson, 1996;Wilkin & Slevin, 2004;Yam & Rossiter, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer gave more importance to affective ''caring actions'' (Radwin, Farquhar, Knowles, & Virchick, 2005), intensive care unit patients felt technical competency and compassion to be of equal importance (Wilkin & Slevin, 2004), and patients in the emergency ward considered the technical aspect of caring as most important (Wiman & Wikblad, 2004). MedicalYSurgical patients were identified as placing greater caring emphasis on physical caring competencies and the ability to deliver a general feeling of well-being (Henderson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%